Towards a Perylene-Containing Nanohoop - Batson, Joel M.; Swager, Timothy M. (Synlett, 2013)
We report the synthesis of a belt-shaped macrocycle, herein referred to as a nanohoop, that contains binaphthyl moieties separated by phenyl groups.
Keywords: macrocycles; arenes; biaryls; Diels–Alder reaction; cyclization